Enhanced dielectric tunability and energy storage properties of plate-like Ba0.6Sr0.4TiO3/poly(vinylidene fluoride) composites through texture arrangement. (12th April 2018) - Wang, Li; Gao, Feng; Xu, Jie; Zhang, Kena; Kong, Jie; Reece, Mike; Yan, Haixue
Abstract: Plate-like (Ba0.6 Sr0.4 )TiO3 (P-BST) particles were synthesized via topochemical microcrystal conversion using a two-step molten salt method. In addition, P-BST/poly(vinylidene fluoride) (PVDF) textured composites were fabricated using a tape casting and hot pressing method. The influence of the P-BST particle size on the microstructure, dielectric tunability, and energy storage properties of the P-BST/PVDF textured composites was investigated. The results revealed that P-BST/PVDF textured composites can be obtained with preferred orientation of plate-like particles, which exhibit uniform directionality in the PVDF matrix. The dielectric properties of these composites increased with increasing P-BST particle size. A new criterion EP 80 was proposed for evaluating the dielectric tunability of composites. The optimal properties of the P-BST/PVDF textured composite (minimum threshold electric field: 14 kV/mm, minimum EP 80 : 29 kV/mm, and maximum energy storage density: 6.36 J/cm 3 ) were realized at a P-BST particle size of 11.47 μm. A dielectric tunability model for inorganic/organic composites with respect to the shape factor ( n ) of the inorganic fillers was proposed and used to simulate the dielectric tunability of the textured composites. For the P-BST/PVDF composite, n of 4–5 in the model corresponded to P-BST particle sizes of 5.19 μm–11.47 μm.